STUDYING OF THE TEMPERATURE MODE OF TANKS AS DEFINING FACTOR OF HYDROCARBONS EMISSIONSAT STORAGE OF OIL PRODUCTS - Яворська, М. В.; Бойченко, С. В.; Черняк, Л. М. (Science-based technologies, 2013)
Considered major factors that significantly affect the loss of petroleum products during storage. Factors which determine the temperature